The New Forms of Pteraspids (Agnatha, Heterostraci) from Podolian Early Devonian - Voichyshyn, V.K. (Вестник зоологии, 1999)
Two new genera and three species and as well as the remains of a new representative of pteraspids described from Lower Devonian ("Old-Red" deposits) of Podolia. The name of the species "Pteraspis" angustata Alth, 1874, are known only from dorsal shields is shown to be valid. Some new terms in pteraspids morphology are proposed. Из красноцветных отложений нижнего девона Подолья описано 2 новых рода и 3 вида, а также остатки нового представителя птераспид. Показано, что название вида "Pteraspis" angustata Alth, 1874, который известен лишь по дорсальным шитам, может считаться валидным. Предлагается использовать некоторые новые термины в морфологии птераспид.